Prevalence of antibodies against Chlamydophila abortus in cattle under extensive system in three districts of Ayacucho, Peru - Loli-Pin, Jean Pierre (2021)
The aim of this study was to determine the prevalence of antibodies against Chlamydophila abortus in cattle from the districts of Coracora, Chumpi and Pullo of the province of Parinacochas, department of Ayacucho, Peru. The animals were raised extensively and under natural breeding. In total, 184 blood samples were taken from cattle over 4 months of age regardless of sex. The detection of antibodies against C. abortus was done with a commercial indirect ELISA kit. A corrected prevalence of 40.34 ± 7.06% was obtained with a significant difference between districts (p<0.05), being lower in Coracora (40.29 ± 8.89%) and higher in Pullo (56.05 ± 7.15%), and without significant differences due to the effect of sex. breed, animal category and reproductive status. The high prevalence confirms the spread of the pathogen in the bovine population of the evaluated districts.